The effects of inorganic and organic Zn, Cu and Mo supplementation to the in vitro digestibility of grass - Supriyati .; D Yulistiani; E Wina; H Hamid; B Haryanto (Jurnal Ilmu Ternak dan Veteriner, 2000)
The effects of inorganic and organic Zn, Cu and Mo supplementation to the in vitro digestibility of Elephant grass were studied in this trial. The in vitro trial used the TILLEY dan TERRY method modified by VAN SOEST with the incubation of the grass for 48 hours in sheep rumen liquor medium. Mineral added as fonn of organic and inorganic. The treatment of mineral inorganic supplementations were by adding single e1emen Cu, Zn and Mo and its combination. Mineral added was Zn (as chloride and sulphate salts) 5 ppm, Cu (sulphate salt) 0,1 ppm dan Mo (molybdate salt) 5 ppm, with 4 replicates. Meanwhile the organic minerals added were in the proteinate fonns. Parameter measured were in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), pH, VF A total and NH3. Statistical analysis was done by using Complete Split splitsplot design. The supplementation increased pH value, VFA total, IVDMD and IVOMD value (P<0,05) and decreased NH3 value. The highest IVDMD and IVOMD values obtained at the mixture supplementation of mineral Zn (as Zn S04), Cu and Mo, from 58,31 became 69.73% and 52.22 became 62.55% respectively for IVDMD and NOMD. pH value increased from 6.48 to 7.05 and ammonia content decreased from 1,17 to 0,14%. The organic mineral supplementation, en-proteinate dan Zn-proteinate showed that the adding of Zn, Zn and Mo, Zn and Cu also the combination of Zn, Cu and Mo, resulted in IVDMD values as 70.29; 69.97, 64.12 and 63.93%. Further more IVDMD value at the supplementation of Cu and the combination of Cu and Mo were 65.08 and 60,49%. It can be concluded that the supplementation of minerals in the form of inorganic or organic could improve the IVDMD values   Key words: Three element, in vitro digestibility, sheep